2015
DOI: 10.1007/s00405-015-3637-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nasopharyngeal microbial flora and antibiogram and its relation to otitis media with effusion

Abstract: Acute otitis media and otitis media with effusion (OME) are the main causes of hearing impairment in children which require proper treatment, mainly antibiotic therapy. Patients whom were appropriate candidates for adenoidectomy were divided into two groups regarding the presence of middle ear effusion. Adenoid tissue specimens were cultured in both groups and the bacterial flora and anti-microbial resistance pattern were determined. 72 patients were studied, 42 % had OME while 58 % did not. The following bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
1
0
1
Order By: Relevance
“…Very high frequency (84%) of MDR strains in our studies has exceeded the data presented in other studies on AOM treatment failure, that 40–67% of pneumococcal strains were MDR [ 32 , 33 ]. Our study have confirmed recent reports showing that antibiotic therapy in AOM induces selection of preexisting nasopharyngeal antibiotic-resistant S. pneumoniae [ 14 , 34 ]. In our study, it was shown that too short time of therapy in children with bilateral AOM, but not of the type of β-lactams has the impact on persistent pneumococcal colonization after treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Very high frequency (84%) of MDR strains in our studies has exceeded the data presented in other studies on AOM treatment failure, that 40–67% of pneumococcal strains were MDR [ 32 , 33 ]. Our study have confirmed recent reports showing that antibiotic therapy in AOM induces selection of preexisting nasopharyngeal antibiotic-resistant S. pneumoniae [ 14 , 34 ]. In our study, it was shown that too short time of therapy in children with bilateral AOM, but not of the type of β-lactams has the impact on persistent pneumococcal colonization after treatment.…”
Section: Discussionsupporting
confidence: 92%
“…The contribution of nasopharyngeal colonizing bacteria to otitis media has been established, and the bacterial pathogens had been studied [26,27]. In our study, there was no difference in antimicrobial use during a recent 2-month period between the case and control groups.…”
Section: Discussionmentioning
confidence: 60%
“…В свете этих данных эффективность аденотомии, сопровождающейся тщательным освобождением указанных областей в условиях эндоскопии, связывается в первую очередь не с удалением избыточно увеличенной лимфоидной ткани, а с элиминацией очага инфекции [7,29,49,50]. Однако показано, что микробиота носоглотки у детей с аденоидитами, ассоциированными с экссудативным средним отитом, и аденоидитами без вовлечения среднего уха практически не различается [51]. Кроме того, отмечено, что если хронический средний гнойный отит практически в 100% случаев сопровождается персистенцией бактериальных пленок в носоглотке, то при хроническом экссудативном отите они выявляются в 3 раза реже, что свидетельствует в пользу мультифакторности заболевания [52].…”
unclassified